THE INFLUENCE OF SERVICE QUALITY AND COMPETENCY ON EMPLOYEE WORK EFFECTIVENESS AT LAUNDRY IN PERCUT SEI TUAN DELI SERDANG DISTRICT - Karim, Ahmad (Strategic Management Business Journal, 2024)
The objectives of this research are to determine the magnitude of the influence of service quality on employee work effectiveness at Laundry in Percut Sei Tuan District, Deli Serdang Regency, determine the magnitude of the influence of competency on employee work effectiveness at Laundry in Percut Sei Tuan District, Deli Serdang Regency, determine the magnitude of the influence of service quality and competence on the work effectiveness of employees at the Laundry in Percut Sei Tuan District, Deli Serdang Regency simultaneously. The number of samples used was 80 people from laudry in Percut Sei Tuan District, Deli Serdang Regency. The analytical method used was quantitative analysis with the help of the SPSS Version 23 program. Research results: Based on the results of hypothesis testing, service quality is proven to have no significant effect on employee work effectiveness. From the hypothesis test, it shows that there is a very small effect, namely 16.5% and the significance value obtained is greater than 0.05, which means the effect is not significant. This can be explained that the dimensions of service quality include: physical evidence, reliability, responsiveness and guarantees which are not able to reflect service quality in influencing employee work effectiveness. Based on the results of hypothesis testing, competence is proven to have a significant effect on employee work effectiveness, the magnitude of the influence of competence on employee work effectiveness is 73.2%, this effect is classified as high. Based on the results of hypothesis testing, service quality and competence together have been proven to have a significant effect on employee work effectiveness. The magnitude of the influence of service quality and competence together on employee work effectiveness is 76.4%, this effect is classified as high. JEL Classification: L2, L8